Relation between the Passing Rate of Students from the Faculty of Medicine and the Evaluation of Teaching Performance in 2017 - Quiroz Condori, Fabiola (2019)
This article reports on the findings of a study that sought to address the relationship between student course evaluations and passing rates of students enrolled at Universidad Federada San Judas Tadeo, School of Medicine in Costa Rica. The study aimed to describe correlations between the different variables measured using an exploratory approach in order to evaluate certain aspects of teacher performance that may affect student learning and academic performance. The study described the type relationship, symmetric or asymmetric, between passing rates and the teacher evaluation performed by the students, from an exploratory approach, in order to establish, from the measured items, the possible components related to teacher classroom performance that may affect student learning and, therefore, their academic performance. The study utilized a quantitative approach with a descriptive method. The information was collected during the three academic quarters in 2017. The research process incorporated the analysis of specific competencies that professors must possess in the development of the teaching process. This study found that teachers of medical sciences are highly competent in their field. There is room for improvement with regard to attitudinal competencies associated with teaching.